Radio frequency identification (RFID) antenna development - Dhimas Sentanu Murti (2012)
Radio Frequency Identification technology can be used for items tracking and inventory management. Such a system will enable the exact number of items in specific storage locations (such as bookshelves, cabinets, drawers etc.) to be detected without the need for physical counting. As a result, it can help to reduce the man-made errors and increase the degree of inventory accuracy.